Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Is there a closed formula for the sum of the first $n$ even (or odd) Fibonacci numbers, like there is one for the $n$th number (Moivre-Binet)?

share|improve this question
1  
See mathforum.org/library/drmath/view/52707.html –  A.E Sep 5 '13 at 21:16
3  
Do you mean the even Fibonacci numbers, or do you mean the Fibonacci numbers with even indices? –  Brian M. Scott Sep 5 '13 at 21:22
1  
Add the Binet formulae for the odds or evens by summing the geometric progressions which arise. Write out the first few terms to see what is going on. –  Mark Bennet Sep 5 '13 at 21:22
1  
@BrianM.Scott the even numbers. But the sum of numbers with even indices would be interesting too. –  user127.0.0.1 Sep 5 '13 at 21:23
1  
Further to @BrianM.Scott's comment - note that every third Fibonacci number is even, so that gives a GP too. The odd numbers can be summed as two GPs (or as the sum of all the numbers less the sum of the even ones). –  Mark Bennet Sep 5 '13 at 21:24
show 6 more comments

2 Answers

up vote 1 down vote accepted

Note that $F_n$ is even iff $n\equiv 0\pmod 3$ because the Fibonacci recursion modulo $2$ gives the sequence $0,1,1,0,1,1,\ldots$

So we want to find a closed expression for $$s_n=\sum_{k=0}^n F_{3k}.$$ We find the recursion (why?) $$s_{n+1} = 4s_n+s_{n-1}+2 $$ and from this $$ s_n =a(2+\sqrt 5)^n+b(2-\sqrt 5)^n -\frac12$$ where $a,b$ can be determined from the cases $n=0$ and $n=1$, for example.

share|improve this answer
    
Note that because $F_{3k}=F_{3k-1}+F_{3k-2}$ it is particularly easy to sum the odd numbers once the sum of the evens is known. –  Mark Bennet Sep 5 '13 at 21:56
add comment

Let $\varphi=\frac12\left(1+\sqrt5\right)$ and $\widehat\varphi=\frac12\left(1-\sqrt5\right)$, so that $F_n=\frac1{\sqrt5}\left(\varphi^n-\widehat\varphi^n\right)$. Then

$$\varphi^3=\left(\frac{1+\sqrt5}2\right)^3=2+\sqrt5\qquad\text{and}\qquad\widehat\varphi^3=\left(\frac{1-\sqrt5}2\right)^3=2-\sqrt5\;,$$

so the sum of the first $n$ even Fibonacci numbers is

$$\begin{align*} \sum_{k=0}^{n-1}F_{3k}&=\frac1{\sqrt5}\sum_{k=0}^{n-1}\left(\varphi^{3k}-\widehat\varphi^{3k}\right)\\\\ &=\frac1{\sqrt5}\left(\sum_{k=0}^{n-1}\varphi^{3k}-\sum_{k=0}^{n-1}\widehat\varphi^{3k}\right)\\\\ &=\frac1{\sqrt5}\left(\frac{\varphi^{3n}-1}{\varphi^3-1}-\frac{\widehat\varphi^{3n}-1}{\widehat\varphi^3-1}\right)\\\\ &=\frac{(2+\sqrt5)^n-1}{5+\sqrt5}-\frac{1-(2-\sqrt5)^n}{5-\sqrt5}\\\\ &=\frac{(2+\sqrt5)^n}{5+\sqrt5}+\frac{(2-\sqrt5)^n}{5-\sqrt5}-\left(\frac1{5+\sqrt5}+\frac1{5-\sqrt5}\right)\\\\ &=\frac{(2+\sqrt5)^n}{5+\sqrt5}+\frac{(2-\sqrt5)^n}{5-\sqrt5}-\frac12\;. \end{align*}$$

Moreover, $2-\sqrt5\approx-0.23607$, and $5-\sqrt5\approx2.76393$, so even for $n=1$ the middle term is only about $-0.08541$, and it decreases rapidly as $n$ increases. Thus, you want the integer nearest

$$\frac{(2+\sqrt5)^n}{5+\sqrt5}-\frac12\;,$$

which is

$$\left\lfloor\frac{(2+\sqrt5)^n}{5+\sqrt5}\right\rfloor\;.$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.